2020
DOI: 10.3389/fbioe.2020.00738
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects With Potential Clinical Importance of Botulinum Toxin Type-A on Mechanics of Muscles Exposed

Abstract: Botulinum toxin type-A (BTX-A) is widely used for spasticity management and mechanically aims at reducing passive resistance at the joint and widening joint range of movement. However, recent experiments on acute BTX-A effects showed that the injected rat tibialis anterior (TA) muscle's passive forces increased, and the length range of active force exertion (l range) did not change. Additionally, BTX-A was shown to spread into non-injected muscles in the compartment and affect their mechanics. Whether those ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…However, the major concern for BoNT injections is the formation of neutralizing antibodies (ranging from 0 to 3.6 %) after repeated treatments, which may jeopardize its therapeutic effects [67] . Alteration of muscle mechanics and intramuscular connective tissue contents were observed in the rat model following BoNT injections [68] . Unintended botulism-like syndrome is possible when hematogenic systemic spread occurs, particularly using a high injection dose [69] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the major concern for BoNT injections is the formation of neutralizing antibodies (ranging from 0 to 3.6 %) after repeated treatments, which may jeopardize its therapeutic effects [67] . Alteration of muscle mechanics and intramuscular connective tissue contents were observed in the rat model following BoNT injections [68] . Unintended botulism-like syndrome is possible when hematogenic systemic spread occurs, particularly using a high injection dose [69] .…”
Section: Discussionmentioning
confidence: 99%
“…67 Alteration of muscle mechanics and intramuscular connective tissue contents were observed in the rat model following BoNT injections. 68 Unintended botulism-like syndrome is possible when hematogenic systemic spread occurs, particularly using a high injection dose. 69 On the contrary, the side effects of ESWT are usually mild, encompassing skin petechial or transient localized pain.…”
Section: Discussionmentioning
confidence: 99%
“…BoNT injections cause chemodenervation effects on the injected spastic muscles via presynaptic blockade of neurotransmitters at the neuromuscular junctions [19][20][21]. Animal studies have shown adaptive changes in the muscles after BoNT injections, including increased collagen content and passive resistance [40,41], muscle fiber loss and atrophy [30]. Collectively, these changes contribute to increased passive stiffness after BoNT.…”
Section: Bont Effects On Elbow Flexor Spastic Hypertoniamentioning
confidence: 99%
“…This altered motor drive and associated limb use, over time, may change muscle structure and function, further amplifying the brain injury induced motor impairments. Botulinum neurotoxin (BoNT) chemical denervation, which is widely used to treat muscle hypertonia and spasticity (20)(21)(22), may also alter muscle properties (23)(24)(25)(26)(27)(28)(29)(30). One particularly detrimental sequelae of these muscle adaptations are that muscles can become increasingly stiff, making movement progressively more difficult.…”
Section: Introductionmentioning
confidence: 99%